From Iquitos/Peru to Parintins/Brazil: urban network and recycling in the Amazon (Brazilian Geographical Journal, 2019)
The Amazon Basin is in a constant urbanization process. Even in isolated areas domestic waste is a problem. How is the recycling market functioning? How are the working conditions of the waste pickers? Can the urban network be understood through the recycling market? These questions oriented field work from Iquitos, Peru to Parintins, Brazil (2011-2014) which evaluated recycling. Due to the almost nonexistence literature a detailed description of the study case is made. As result, the market structure was divided into three different nodules: Lima (Peru), Bogotá (Colombia) and São Paulo (Brazil). Each nodule has different approaches of what is recycled and how. It was observed an intense informal market for recycling with no workers-rights and low incorporation of technology with restricted materials recycled, mainly aluminum. What and how innovations in recycling technology and market structure can be introduced in the area that can transform reality is a central question.